2007
DOI: 10.1029/2006jd007277
|View full text |Cite
|
Sign up to set email alerts
|

Intercomparison of SCIAMACHY nitrogen dioxide observations, in situ measurements and air quality modeling results over Western Europe

Abstract: [1] The Scanning Imaging Absorption Spectrometer for Atmospheric Cartography (SCIAMACHY) satellite spectrometer provides detailed information on the nitrogen dioxide (NO 2 ) content in the planetary boundary layer. NO 2 tropospheric column retrievals of SCIAMACHY and its predecessor Global Ozone Monitoring Experiment are characterized by errors of the order of 40%. We present here a new SCIAMACHY tropospheric retrieval data set for the year 2003. The cloud free satellite observations are compared to surface me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
119
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(120 citation statements)
references
References 82 publications
1
119
0
Order By: Relevance
“…The model is also used for forecasts of pollutant levels as part of the French national air pollution forecasting system, Prev'Air (www.prevair.org). CHIMERE has been extensively validated with surface and airborne measurements for the different scales (Schmidt et al, 2001;Blond and Vautard, 2004;Menut et al, 2000;Vautard et al, 2003;Blond et al, 2007;Honoré et al, 2008). As an example, the averaged bias for daily ozone maxima over Europe is smaller than 10% (Honoré et al, 2008).…”
Section: Model Descriptionmentioning
confidence: 99%
“…The model is also used for forecasts of pollutant levels as part of the French national air pollution forecasting system, Prev'Air (www.prevair.org). CHIMERE has been extensively validated with surface and airborne measurements for the different scales (Schmidt et al, 2001;Blond and Vautard, 2004;Menut et al, 2000;Vautard et al, 2003;Blond et al, 2007;Honoré et al, 2008). As an example, the averaged bias for daily ozone maxima over Europe is smaller than 10% (Honoré et al, 2008).…”
Section: Model Descriptionmentioning
confidence: 99%
“…The impact of topography on SCIAMACHY NO 2 retrievals was investigated by Schaub et al (2007) who found errors of up to 40 % over very complex terrain. Blond et al (2007) intercompared SCIAMACHY-based NO 2 retrievals with in situ station observations over Europe and found biases of less than 5 % and 20 % for annual and seasonal averages, respectively.…”
Section: Satellite Datamentioning
confidence: 99%
“…We have selected 17 rural stations as their measurements are considered most representative for the regions comparable to the coinciding model grid (Blond et al, 2007). The corresponding model results have been interpolated in space and time to these measurement sites.…”
Section: Comparison To In-situ Observations In the Netherlandsmentioning
confidence: 99%
“…It highlighted the differences in the models, but also showed significant differences between the retrieval algorithms. A more detailed analysis on a 0.5 • grid for a regional model (CHIMERE) using the SCIAMACHY NO 2 data and surface observations was presented by Blond et al (2007). In these studies some of the differences between models as well as differences of models compared to NO 2 retrievals remained unclarified.…”
Section: Introductionmentioning
confidence: 99%